Diseño de un plan de negocio para una empresa de catering con empaques biodegradables direccionada al sector ejecutivo de la ciudad de Latacunga. - Cevallos Bartelotti, Mayra Alejandra (2020)
The objective of this present project is to determine the feasibility of creating a catering company with biodegradable packaging for the executive sector of public and private companies in Latacunga city. The introduction followed by the theoretical foundation, the strategic part of the enterprise where the mission, vision, corporate values, principles, policies, canvas model, business were determined. In the market investigation, the segmentation was determined where the target market for the enterprise was obtained, size of the sample model of survey, analysis and interpretation of data where the tastes and preferences of the products were determined, which were the sanduche, the empanadas, and the mote with chicharrón and unsatisfied demand, and thus we obtained the unsatisfied demand.in the Technical Study it is taken the decision of the % in the market and so know all the necessary aspects for the operation of the enterprise where it is going to be placed, distribution of the plant, based on this the different strategies of the marketing mix were applied. The Economic and Financial study, where all resources for the project were analyzed with an initial investment of $12320,02 from the statement of results, it was analyzed that in the first year of execution we will get a net profit of $9424,20, as in the general balance we have that our accounts payable in year 1 would be $3139,79 analyzed different financial indicators as the current minimum rate of return 58%, the period of return on investment will be achieved in 18 months at a current minimum rate of return of 7.77%. with a relation benefit cost of $1.10 which makes this project viable